Retos del cine mexicano comercial para su consumo en los Estados Unidos (Mexican commercial film challenges for its consumption in the United States) - Lozano Treviño, David Fernando; Barragán Codina, José Nicolás; Guerra Moya, Sergio Armando; Villalpando Cadena, Paula (Facultad de Contaduría Pública y Administración U.A.N.L., 2010)
Abstract: The main purpose of this document is to give statement of the importance that the innovative ideas of the Mexican commercial films organizations have, so they can create attractive movies for the spectators in the United States market and increase the film business. Also, we discuss the need that the organizations have to create production plans that allow them to reduce the costs, as much as possible, during the production. This will be the beginning to develop an appropriate commercializing into the United States by the Mexican organizations that will allow us to obtain an attractive revenue, always looking towards the United State customers´ satisfaction. Finally, we analyze the critical factors of success or failure in the Mexican commercial film productions, taking into account the financial aspects, like the production investment, government supports and the return over the investment; the international marketing, that includes the film promotion and the distribution and exhibition; and the artistic aspect composed by the human talent and the movie story.